Penataan Permukiman Terdampak Banjir Rob Dengan Penerapan Konsep Rumah Terapung - erislianautarinurfadillah sihombing; Novalinda; Faurantina Forlana Sigit; Rahmadhani Fitri (Universitas Medan Area, 2023)
The main impact resulting from sea level rise is the occurrence of high tides which result in tidal flooding to community settlements in Bagan Deli Village. This phenomenon has a negative impact on improving the quality of life indicators in a settlement. Inadequate house shape to prevent tidal flooding and irregular spatial patterns are factors in this research. The purpose of this study is to produce a floating house arrangement design solution which is expected to be a solution for areas affected by tidal flooding. This research method uses a pattern of circulation forms that already exist in Bagan Deli Village and applies the concept of a floating house design with architectural design principles. The results of this study will be published so that it can become a theoretical basis for the community and government in improving the quality of the community environment affected by the tidal flood.